Ijaz Al-Quran dalam Pandangan Muktazilah - Idris Siregar; Shofiyatun Nafisah Lubis; Alhafiz Alhafiz (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
Ijaz Al-Quran or miracles of the Al-Quran is a concept that emphasizes the superiority and uniqueness of the Al-Quran which cannot be matched by humans. In the view of the Muktazilah, a school of Islamic theology that developed in the 8th to 10th centuries AD, Ijaz Al-Quran is analyzed through a rational and theological approach. Muktazilah emphasized that the miracle of the Al-Quran lies in aspects of its language, rhetoric and scientific content which exceed ordinary human abilities. Muktazilah believes that the superiority of the Al-Quran in the linguistic aspect is clear evidence of human inability to produce something comparable. They also consider the harmonious structure and composition of the Al-Quran, as well as the scientific accuracy found therein, to be strong evidence of divine revelation. In view, the miracles of the Al-Quran also include its ability to influence and change human behavior and beliefs. Even though the Muktazilah used a rational approach in interpreting the ijaz of the Al-Quran, they still acknowledged that the main source of this miracle was Allah. They argue that the use of reason and reasoning in understanding the superiority of the Al-Quran does not reduce the spiritual value and belief in revelation. Thus, the Muktazilah's view of the ijaz of the Al-Quran reflects a balance between rationality and spirituality in their theological understanding.